Optimal sites for orthodontic anchor screw placement using panoramic images: risk of maxillary sinus perforation and contact with adjacent tooth roots during screw placement - Ken Miyazawa; Momoko Shibata; Masako Tabuchi; Misuzu Kawaguchi; Noriko Shimura; Shigemi Goto (SpringerOpen, 2021)
Abstract Objectives This study investigated the safety of orthodontic anchor screw (OAS) placement by examining the morphology and degree of depression of the maxillary sinus adjacent to the alveolar bone between the maxillary molars. Methods We reviewed panoramic and CT imaging data of 25 patients. First, the morphology of the maxillary sinus adjacent to the alveolar bone between the maxillary molars on panoramic images was classified into three types: non-depressed sinus, funnel-like sinus depression, and sawtooth-like sinus depression. Then, the distance from the maxillary buccal bone to the maxillary sinus or to the maxillary lingual bone and the distance between the roots of the maxillary second premolar and first molar at heights of 5, 6.5, and 8 mm from the alveolar crest were measured on CT images and compared between the three sinus morphology groups. Results The sawtooth-like depression group had significantly smaller bone thickness than the other two groups, with mean thickness of < 4 mm at any height from the alveolar crest. The funnel-like depression and non-depression groups had mean bone thickness of > 8 mm at any height from the alveolar crest. Conclusions Sawtooth-like sinus depression had increased risk of maxillary sinus perforation, suggesting that OAS placement in this region should be avoided. In contrast, OAS placement between 6.5 and 8 mm from the alveolar crest is advisable in patients with funnel-like sinus depression and at a site > 8 mm from the alveolar crest in those with a non-depressed sinus.